Ballets and Representation of Power in Piedmont in the 17th Century: Costumes for the Dancing Court - Cacia, Daniela (ZoneModa Journal, 2023)
The National Library and the Royal Library of Turin hold thirteen manuscripts that reproduce as many performances, staged at the Savoy court between 1640 and 1681. The manuscripts reflect the artistic, cultural and political climate of 17th-century Turin and also include descriptions of the costumes worn by the performers, along with a rich collection of images. The captions and depictions thus provide a valuable source for the study of fashion and clothing of the period. More specifically, the contribution focuses on the attire worn by Duke Carlo Emanuele II in the ballets and the lexicon of clothing in use at the time. The work brings visibility to texts that are still largely unpublished.